Evaluation of microbial contamination and effects of storage in raw meat‐based dog foods purchased online. Issue 2 (2nd December 2019) - Morelli, Giada; Catellani, Paolo; Miotti Scapin, Riccardo; Bastianello, Sofia; Conficoni, Daniele; Contiero, Barbara; Ricci, Rebecca
Abstract: Feeding raw‐meat‐based diets to companion animals has become a widespread practice, and many owners are now accustomed to buying frozen ingredients online. The goals of this study were to assess the microbiological quality of raw‐meat dog foods obtained from specialized websites and to evaluate the effects of storage at different temperatures for a few days. Twenty‐nine raw dog food products were processed for quantitative bacteriology (i.e. total viable count, TVC; Escherichia coli ; faecal coliforms, FC) and sulphite‐reducing clostridia, and analysed for the presence of Salmonella spp., Listeria monocytogenes, Yersinia enterocolitica and Clostridium difficile . Every sample was examined right after the delivery (T0), after 24 to 48 hr and after 72 hr, both at 2°C and 7°C. At T0, the mean score for the TVC was 5.9 × 10 6 cfu/g ( SD = 4.8 × 10 7 cfu/g), while those for E. coli and FC were 1.1 × 10 4 cfu/g ( SD = 2.5 × 10 5 cfu/g) and 3.3 × 10 3 cfu/g ( SD = 6.5 × 10 4 cfu/g) respectively. The samples stored at 2°C had a significant increase of all parameters (TVC: p < .01; E. coli : p = .03; FC: p = .04) through time. Noteworthy differences between the analyses performed at 2°C and 7°C were found for TVC ( p < .01), being the samples considerably more contaminated at higher temperatures. No sample tested positive for Salmonella spp., while L. monocytogenes was isolated from 19 products, Y. enterocolitica from three products and Clostridium perfringens and C. difficile from four and six products respectively. The microbiological quality of raw‐meat dog foods sold online appears to be poor, carrying considerable amounts of potentially zoonotic bacteria and reaching greater levels of bacterial contaminations if not kept at proper refrigeration temperatures and fed soon after defrosting.